The aesthetic alternative.: Romanticism in the face of the reception of Kantian criticism - Miñambres, Germán Garrido (Revista de Filosofía, 2021)
This paper sets the origin of German early Romanticism in the context of Kant’s reception. We focus on three debates about transcendental philosophy: the existence of a first principle of knowledge; the link between theoretical and practical philosophy; and the relationship between beauty and morality. This approach allows us to see the Romantic aesthetics as a critical theory with its own foundation, method and purpose. This sheds light on the influence of Romanticism on literary theory and criticism.